In situ Viscometry of Primitive Lunar Magmas at High Pressure and High Temperature - Rai, Nachiketa; Perrillat, Jean-Philippe; Mezouar, Mohamed; Colin, Aurélia; Petitgirard, Sylvain; van Westrenen, Wim (Frontiers in Earth Science, 2019)
Understanding the dynamics of the magmatic evolution of the interior of the Moon requires accurate knowledge of the viscosity () of lunar magmas at high pressure (P) and high temperature (T) conditions. Although the viscosities of terrestrial magmas are relatively well documented, and their relation to magma composition well studied, the viscosities of lunar titano-silicate melts are not well known. Here, we present an experimentally measured viscosity dataset for three end member compositions, characterized by a wide range of titanium contents, at lunar-relevant pressure-temperature range of 1.1 – 2.4 GPa and 1830 - 2090 K. In-situ viscometry using the falling sphere technique shows that the viscosity of lunar melts varies between  0.13 and 0.87 Pa-s depending on temperature, pressure and composition. Viscosity decreases with increasing temperature with activation energies for viscous flow of Ea = 201 kJ/mol and Ea = 106 kJ/mol for low-titanium (Ti) and high-Ti melts, respectively. Pressure is found to mildly increase the viscosity of these intermediate polymerized melts by a factor of  1.5 between 1.1 and 2.4 GPa. Viscosities of low-Ti and high-Ti magmas at their respective melting temperatures are very close. However at identical P-T conditions ( 1.3 GPa,  1840 K) low-Ti magmas are about a factor of three more viscous than high-Ti magmas, reflecting structural effects of Si and Ti on melt viscosity. Measured viscosities differ significantly from empirical models based on measurements of the viscosity of terrestrial basalts, with largest deviations observed for the most Ti-rich and Si-poor composition. Viscosity coefficients for these primitive lunar melts are found to be lower than those of common terrestrial basalts, giving them a high mobility throughout the lunar mantle and onto the surface of the Moon despite their Fe and Ti-rich compositions.